SOME REFLECTIONS ON COMMUNICATIVE APPROACH, POSTMETHOD AND TEACHING PRACTICE - Vieira Abrahao, Maria Helena [UNESP] (Unesp-faculdade Ciencias & Letras, 2015)
This article brings some reflections on communicative approach, post-method and teaching practice. It starts with a brief overview of principles which guide both approaches, makes a comparison between them, pointing at several common points which characterize them not as excludent approaches, but complementary ones. It also includes, in this reflection, an evaluation of the same approaches by applied linguistics graduate students in which they take into account their positive and negative aspects in theoretical and practical levels. Finally, implications for teacher education are brought.
Keywords: Foreign language teaching; Communicative approach; Postmethod; Pragmatism based on principles; Teacher autonomy